Mapping Location of The Former Land of The Unlicensed Gold Mining (Ugm) in A Several Subdistricts in Kuantan Singingi District - Sri Mulyani; Raisa Baharuddin; Defri Kurnia Putra Sidiq; Anandyawati Anandyawati (TERRA : Journal of Land Restoration, 2020)
Public gold mining carried out without permission and not organized is rife in Riau. Until now there is still lack of information about Unlicensed Gold Mining (UGM) in Kuantan Singingi District specifically Singingi subdistrict, Kuatan Tengah, Sentajo Raya and Logas Tanah Darat. The former gold mining land cannot be used for agricultural activities. To overcome this problem reclamation needs to be done on the former gold mine land. However, before the step is taken, the initial step is mapping the point of the location of the former gold mine, general conditions, land ownership status and mining processes, vegetation in UGM land and the impact of UGM in Singingi subdistrict, Kuatan Tengah, Sentajo Raya and Tanah Darat Logas. This study aims to map the distribution of land of the former gold mine, determine general conditions, land ownership status and mining processes, vegetation of former UGM land and the impact of UGM in Singingi District, Central Kuatan, Sentajo Raya and Tanah Darat Logas, in Kuantan Singingi District. The parameters observed were: point of distribution of the location of the former gold mine, general conditions, land ownership status and the mining process, vegetation of former UGM land and the impact of UGM. The results showed that in all subdistricts sample namely Singingi, Kuatan Tengah, Sentajo Raya and Tanah Darat Logas in Kuantan Singingi Distric there were unlicensed gold mining along the river flow area. Overall land ownership status is owned by individuals/individuals (people with capital) and land used for mining activities that are owned by others rent. There are three types of species that grow on the former gold mine land that is Melastoma malabathricum L., Cyperus halpan L. and Scleria sumatrensis Retz. While the real impact of unlicensed gold mining activities is the loss of river water bodies.